Graphic novel backpack. The Baby-sitters Club. Volumes 1-6. - Telgemeier, Raina; Galligan, Gale.; Martin, Ann M., 1955-; Sonoma County Library (Rohnert Park, Calif., 2020)
Kristy, Mary Anne, Claudia, and Stacey are best friends and founding members of the Baby-Sitters Club. Whatever comes up -- cranky toddlers, huge dogs, scary neighbors, prank calls -- you can count on them to save the day. Baby-sitting isn't always easy, and neither is dealing with strict parents, new families, fashion emergencies, and mysterious secrets. But no matter what, the BSC have what they need most: friendship.
V. 1. Kristy's great idea -- V. 2. The truth about Stacey -- V. 3. Mary Anne saves the day -- V. 4. Claudia and mean Janine -- V. 5. Dawn and the impossible three -- V. 6. Kristy's big day.
Pack compiled by Sonoma County Library.
Keywords: Babysitters Club (Imaginary organization) -- Comic books, strips, etc; Babysitters -- Comic books, strips, etc; Clubs -- Comic books, strips, etc; Friendship -- Comic books, strips, etc; Babysitters Club (Imaginary organization) -- Juvenile fiction; Babysitters -- Juvenile fiction; Clubs -- Juvenile fiction; Friendship -- Juvenile fiction